Effects of different doses of Plant-Growth-Promoting Rhizobacteria (PGPR) granules on wheat yield - Devkota, Sabina; Rayamajhi, Kamana; Yadav, Dil Raj; Shrestha, Jiban (Journal of Agriculture and Natural Resources, 2020)
Plant growth promoting rhizobacteria (PGPR) are the soil bacteria inhabiting around/on the root surface and are directly or indirectly involved in promoting plant growth and development. This study was conducted at research field of Agriculture Research Station, Belachapi, Dhanusa, Nepal in 2018 to identify the effects of PGPR on wheat production. The experiment was laid out in Randomized Complete Block Design with three replications. Eight treatments namely, T1: Control; T2: Recommended doses of fertilizers (RDF) (100:50:50 N:P2O5:K2O kg/ha); T3:10 t/ha Farm Yard Manure (FYM); T4: PGPR 12.5 kg/ha ; T5: PGPR 25 kg/ha; T6: PGPR 7 kg/ha; T7: PGPR 12.5 kg/ha + ½ RDF; T8:  PGPR 7 kg/ha + ½ FYM, were applied in this experiment. Wheat variety NL-971 was used. The results showed that the thousand grain weight showed significant result. The treatment with 10 t/ha FYM was found the best for spike length (8.267cm), grains per five spikes (160) and Thousand grain weight (49.28 g).  Whereas, the highest yield (2.064 t/ha) was obtained with application of PGPR 7 kg/ha + ½ FYM. The PH content was found the highest (5.453) with application of RDF. The maximum organic matter content (1.763) and N content (0.1179%) were found with application of PGPR 12.5 kg/ha. Similarly, the highest phosphorus content (75.83 mg/kg) was found with application of PGPR7 kg/ha while the highest potassium content (72.51 mg/kg) was obtained with application of PGPR 25kg/ha. Overall, there was positive impact of application of PGPR on wheat production.